IMPLEMENTASI METODE SCRUM DAN ANALISIS SWOT SEBAGAI STRATEGI FRAMEWORK CUSTOMER RELATIONSHIP MANAGEMENT(CRM) PADA PERUSAHAAN RENTAL MOBIL - Emi Sita Eriana; Afrizal Zein (Institut Sains dan Teknologi Nasional, 2021)
The rapid competition of business, it is necessary to implement the right strategies to support its business processes, one of which is through customer relationship management, with the aim of creating customer loyalty. Loyalty is expected to be done, ranging from customers who are looking for information to finish getting the service. The application of Customer Relationship Management (CRM) is the right alternative solution to realize customer loyalty. Implement an e-CRM system by applying scrum methods and SWOT analysis. The SCRUM method is software that includes agile development that uses an object-oriented approach and includes planning, design, coding, and testing activities. Implementation of Scrum Modeling with three phases: pregame, scrum phase, post-game. After the application is evaluated with the SWOT method maximizes strengths and opportunities, but can simultaneously minimize weaknesses and threats, from the sprint process that has been completed reviewed, and changes are needed. Website-based e-CRM system application that facilitates customer service and mamou affects customer loyalty and can support business processes on S2 Trans Karawang service. Keywords: Customer Relationship Management (CRM), Business, Customer, SWOT Analysis, Information